PUPUK ORGANIK CAIR DARI SAMPAH SAYURAN PADA PRODUKSI KACANG TUNGGAK (Vigna unguiculata L.) - Muliaty Galib; Anwar Robbo (Percetakan Umi Toaha Makassar, 2022)
Vegetable waste that is wasted can be used as liquid organic fertilizer in an effort to reduce the use of inorganic fertilizers that can damage the environment. This study aims to study the effects of dose and time of application of liquid organic fertilizer from vegetable waste on cowpea plants. This research was conducted in Antang village, Manggala district, Makassar, South Sulawesi. This research was arranged in a randomized block design with a factorial pattern consisting of 2 factors. The first factor was the dose of liquid organic fertilizer, which consisted of 4 levels, namely: control, 5 cc/l, 10 cc/l, and 15 cc/l. The second factor was the time of administration. Spraying in the morning and spraying in the afternoonThe results showed that in the afternoon, the application of liquid organic fertilizer from vegetable waste had an effect on the production of cowpea plants. The parameters of the highest seed weight obtained were 21.48 g and weight per 100 plant seeds obtained the highest yield of 10.13 g.